On problems concerning the teaching of literature - Rosa W. Konder (Ilha do Desterro)
When asked by the editor of this periodical to contribute an article to this issue, on the place of English literature in the syllabus of the UFSC letters course, I felt reluctant to do it because I did.not belong to the area. Then I realised that what he wanted was exactly this: the views of an outsider. A non-specialist may sometimes see more clearly what deficiencies exist in a discipline in which he is not involved. Although I do not at all claim to know what is right and what is wrong in the teaching of English literature in our letters course, I will raise two sets of related questions to be discussed. In the first set the questions are concerned with the courses which are now being given. In the second, some theoretical and methodological issues will be discussed. It is assumed that when teachers get together to device programmes for a course they will first of all discuss the students' needs both in terms of what knowledge of the subject in question they must acquire so as to become competent professionals and also in terms of the policy to be followed for the goal considered adequate to their needs to be attained. In the specific case of the teaching of English literature, and taking for granted that learning literature is important for a number of reasons, these questions seem relevant.